Circuit Simulation Considering Electrical Coupling in Monolithic 3D Logics with Junctionless FETs - Tae Jun Ahn; Yun Seop Yu (Micromachines, 2020)
The junctionless field-effect transistor (JLFET) compact model using the model parameters extracted from the LETI-UTSOI (version 2.1) model was proposed to perform circuit simulation considering the electrical coupling between the stacked JLFETs of a monolithic 3D integrated circuit (M3DIC) composed of JLFETs (M3DIC-JLFET). We validated the model by extracting the model parameters and comparing the simulation results of the technology computer-aided design and the Synopsys HSPICE circuit simulator. The performance of the M3DIC-JLFET was compared with that of the M3DIC composed of MOSFETs (M3DIC-MOSFET). The performance of a fan-out-3 ring oscillator with M3DIC-JLFET varied by less than 3% compared to that with M3DIC-MOSFET. The performances of ring oscillators of M3DIC-JLFET and M3DIC-MOSFET were almost the same. We simulated the performances of M3DICs such as an inverter, a NAND, a NOR, a 2 × 1 multiplexer, and a D flip-flop. The overall performance of the M3DIC-MOSFET was slightly better than that of the M3DIC-JLFET.